Impacts of urban scale on low-carbon development: evidence from 265 cities in China - Guo, Ruibing; Zhao, Jun; Liu, Xinyu; Zhang, Jinning (Frontiers in Environmental Science, 2024)
With rapid urbanization and increasing greenhouse effect, low-carbon development is the integral factor of achieving sustainable development. A comprehensive analysis framework is built to quantify the impact of urban scale on low-carbon development and we conduct empirical research on 265 cities during 2009–2019. We find that: first, urban scale can significantly promote low-carbon development and this finding still holds after the robustness test. Specifically, for every 1% increase in urban scale, the low-carbon development level of the urban increases by 0.128%; second, urban scale promotes low-carbon development mainly through three paths: efficiency improvement, industrial structure upgrading, and innovation; third, there is heterogeneity in this effect among cities with different city levels, city structures, and traffic conditions. Therefore, we propose specific, targeted policy implications, including reducing restrictions on the expansion of large cities and promoting high-tech development.